2010
DOI: 10.1002/macp.200900464
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Novel PEAs Containing Two Consecutive Amide Bonds Randomly Distributed Along the Polyester Backbone

Abstract: The morphology of a series of novel segmented PEAs with varying amide content was studied by a combination of DSC, SFM and proton solid state NMR. Semicrystalline polymers organised in a lamellar morphology were obtained for all amide contents. The results of different NMR experiments revealed that a three phase system composed of a rigid phase, an interface and a mobile amorphous phase is the most appropriate model to describe the morphology of these materials. The amount, the chain dynamics and the domain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…Since the objective of including polyamide is to take advantage of its strongly bonded crystals it would seem that the long amide sequence is preferred. Subsequently, Garg et al [219] reported on the morphology of the copolymer with two-amide sequences. Thermoplastic elastomers are a class of block copolymers in which periodic crystallizable ''hard'' segments are interspersed with ''soft'' segments, each of the latter consisting of a long block of non-crystallizing polymer.…”
Section: Copolymerization With Non-amidic Monomersmentioning
confidence: 98%
“…Since the objective of including polyamide is to take advantage of its strongly bonded crystals it would seem that the long amide sequence is preferred. Subsequently, Garg et al [219] reported on the morphology of the copolymer with two-amide sequences. Thermoplastic elastomers are a class of block copolymers in which periodic crystallizable ''hard'' segments are interspersed with ''soft'' segments, each of the latter consisting of a long block of non-crystallizing polymer.…”
Section: Copolymerization With Non-amidic Monomersmentioning
confidence: 98%
“…14−16 The melting and crystallization temperatures were also reported as part of the thermal properties. 17,18 To the best of our knowledge, there is a lack of crystallization studies on PEAs based on crystalline aliphatic polyesters and amorphous aromatic polyamides.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The polyester and polyamide used in their work were poly­(hexamethylene terephthalate) and poly­(hexamethylene terephthalamide), respectively, both of which have poor biodegradability. Furthermore, DSC data, from which distinct melting and crystallization temperatures were observed for polyesters and polyamides, were used to confirm the blocky microstructure. The melting and crystallization temperatures were also reported as part of the thermal properties. , To the best of our knowledge, there is a lack of crystallization studies on PEAs based on crystalline aliphatic polyesters and amorphous aromatic polyamides.…”
Section: Introductionmentioning
confidence: 99%